PENYELESAIAN TERHADAP TINDAKAN WANPRESTASI ANTARA PEMILIK KOS DENGAN PENGHUNI KOS - Infitahatun Nimah; Nur Amaliyah Purwitasari (JOURNAL SAINS STUDENT RESEARCH, 2023)
A boarding houe rental agreement is a from of agreement that often occurs in society. The agreement regulates the rights and abligations between the boarding house owner and the boarding house occupants. One of the actions that is often carried out by one of the parties in a boarding house rental agreement is default. Default is a situation where one of the parties as agreed does not fulfil its obligation as agreed upon properly. It there is a breach of contract between the boarding house occupantas, the mouse frequent occurrence is not paiying the boarding house rental money, leaving the goods after the rental period has expired, damaging the boarding house facilities. In the case, the boarding house owner can demand that the boarding house occupants pay the boarding house rent in arrears, as well as compensate for the losses they have experienced. Apart form that, boarding house resident who commit default by damaging boarding house facilities or not maintaining the boarding room properly, in this case the boarding house owner can also sue the boarding house resident to compensate for losses. The boading house owner can file a lawsuit for breach of contract against the occuans in court. A lawsuit for breach of contract can be filed in civil or criminal manner. A civil lawsuit can be filed to request fulfillment of compensation obligations or cancellation of the agreement. A criminal complaint can be filedto charge boarding house residents with human prison.